Odessa - Iepan, Florin (Romania : Starcrest Media GmbH, 2010)
The Odessa massacre took place in October 1941 when, at the behest of Marshal Ion Antonescu, the Romanian Army killed, according to director Florin Iepan, more than 22,000 Jewish civilians.
The movie "Odessa," explores how Romania's political and intellectual elite refuse to address their country's involvement in the Holocaust, not to mention engage in a public debate about who was responsible and how it ought to be remembered.
Keywords: Documentary films